Tanggalkanlah Kasutmu! Romo Shadeg dan Budaya Bali - Sudhiarsa, Raymundus I Made (Perspektif, 2007)
Fr. Norbert Shadeg, SVD (1921-2006), an American by birth, was one of the longest foreign missionaries worked in Bali, a place he loved so dearly and the people he served so passionately. For 56 years he spent his priestly life in his allur new 'adopted home' not only for the local Church but also for the host culture, hopes its people and language, its customs and religiosity, etc. His works are highly Fappreciated by many, his colleagues, friends, Christian congregations and his confreres of the Divine Word Missionaries (SVD). His dictionaries are used per worldwide, such as 'A Basic Balinese Vocabulary, 'Bali Pocket Dictionary, and the latest one 'Balinese-English Dictionary (2007). This article tries to find out the so-called 'mission spirituality' on which he built up his missionary life and dedicated his whole life for Balinese society. As priest, teacher, and curator of culture he devoted his life based on the spirit of service like of Moses' spirituality, namely 'to take off his sandals, because he is standing on holy ground' (cf. Ex. 3:5). As a missionary who got his Indonesian citizenship in 1981, Fr. Norbert spent his talents to participate in preserving and promoting Balinese culture and language. No doubt he was an extraordinary person who deserves respect and appreciation from everybody. Most of all, he bequeathed a lot of precious things to the Church's present generation. Without hesitation the Church as an integral part of the Balinese society should carry on this responsibility for the betterment of all.